Sources of information available to senior secondary school student on the nutritional practices adopted in Delta State, Nigeria - Oghenevwarhe Itagar; Juliana Ego Azonuche; Diana Oritsegbubemi Arubayi (PT. Pena Produktif Kreatif, 2026)
Promoting healthy eating among youth is hindered by limited access to reliable dietary guidance, which often leads to poor nutritional practices and adverse long-term health outcomes among adolescents. This study adopted an ex-post facto, descriptive survey design in Delta State, Nigeria. Out of a population of 14,819 public senior secondary students across three senatorial zones, a sample of 390 students from 18 schools was selected using Slovin’s formula and multistage sampling. Data was collected via a validated, 4-point Likert scale questionnaire (Cronbach’s Alpha = 0.81) with a 100% retrieval rate. Analysis involved percentages, mean scores, standard deviations, and t-test statistics using SPSS version 22. Based on 390 respondents, senior secondary students agreed that television (M = 3.47), friends/classmates (M = 3.26), radio (M = 2.90), and social media (M = 2.76) are available nutritional information sources, exceeding the 2.50 cut-off. Conversely, they disagreed on home economics textbooks, newspapers, and fiction books (M = 2.23 – 2.40). Standard deviations ranged from 0.63 to 0.99. Hypothesis testing revealed a significant locational difference in information sources between urban (N = 219, M = 21.42, SD = 2.62) and rural (N = 171, M = 12.35, SD = 2.38) students. With t-cal = 35.32 and p = 0.00 (at alpha = 0.05), the null hypothesis was rejected. In conclusion, secondary students rely heavily on electronic and social media for nutritional knowledge, while print media remains ineffective. Significant urban-rural disparities highlight the urgent need for equitable, localized nutritional interventions.